Financial development, government bond returns, and stability: International evidence - Boubaker, Sabri; Nguyen, Duc Khuong; Piljak, Vanja; Savvides, Andreas (My University, 2019)
This paper investigates the effect of financial development on government bond returns in developed and emerging markets under different market conditions. Using a quantile regression framework for quarterly panel data from 28 countries over 1999–2015, our results reveal that the effect of financial development on government bond returns (changes in bond prices) differs according to conditions in the market and between developed and emerging markets. The effect is positive and significant only in good market conditions for developed markets. For emerging markets financial development has a positive and significant effect for good market conditions but the effect is negative and significant for bad market conditions.
Keywords: Emerging markets; Financial development; Government bond markets; Quantile regression